High‐Resolution Microendoscope Images of Middle Ear Cholesteatoma and Surrounding Tissue: Evaluation of Interobserver Concordance. (10th January 2014) - Bradley, James; Jiang, Nancy; Levy, Lauren; Richards‐Kortum, Rebecca; Sikora, Andrew; Smouha, Eric
Abstract : Objective: Investigate how accurately otolaryngologists could differentiate between images obtained with high‐resolution microendoscopy (HRME) of ex vivo cholesteatoma specimens and surrounding middle ear epithelium. Study Design: HRME images of surgically resected cholesteatoma and middle ear epithelium were obtained and otolaryngologists classified these images. Setting: Tertiary medical center. Subjects and Methods: Resected cholesteatoma and middle ear epithelium were stained with a contrast agent, proflavine, and HRME images were captured. Specimens were sent for standard histopathology and compared with HRME images. Quality‐controlled images were used to assemble a training set. After viewing training images, otolaryngologists without prior cholesteatoma HRME experience reviewed and classified test images. Results: Ten cholesteatoma and 9 middle ear specimens were collected, of which 17 representative cholesteatoma and 19 middle ear epithelium images were extracted for a testing set. Qualitative analysis for concordance between HRME images and histological images yielded a strong correlation between modalities. The mean accuracy of all reviewers in correctly identifying images was 95% (95% confidence interval [CI], 92%‐98%). The sensitivity to correctly detect cholesteatoma images was 98% (95% CI, 93%‐100%), and the specificity was 92% (95% CI, 87%‐97%). The Fleiss kappa interrater reliability score was 0.83, (95% CI, 0.77‐0.89). Conclusions: Medical professionals can quickly be trained to accurately distinguish between HRME images of cholesteatoma and normal middle ear epithelium, both of which have distinct imaging characteristics. Real‐time HRME optical imaging can potentially improve the results of otologic surgery by allowing for extirpation of cholesteatomas while eliminating residual disease.